Biodemography - Carey, James R. (Henry Stewart Talks, 2024)
Demography and biodemography, Lifespan concepts and evolutionary concepts, Natural history of lifespan, Lifespan overview, Coevolution of longevity and sociality, Lifespan in humans, Oldest persons and life expectancy